The Windsor Magazine. (Londen : Ward Lock & Co Limited, 1895)
The Windsor Magazine was a monthly illustrated publication produced by Ward Lock & Co from January 1895 to September 1939 (537 issues).The title page described it as "An Illustrated Monthly for Men and Women" (Wikipedia)
Https://en.wikipedia.org/wiki/The_Windsor_Magazine
Indexen: https://victorianfictionresearchguides.org/the-windsor-magazine
Online: https://archive.org/search.php?query=the%20windsor%20magazine
Engels
Tijdschriften